Lipolytic Activity of Svetol®, a Decaffeinated Green Coffee Bean Extract. (12th December 2013) - Flanagan, John; Bily, Antoine; Rolland, Yohan; Roller, Marc
<x xml:space="preserve">Abstract</x> The beneficial health effects of chlorogenic acids (CGAs), major components of coffee beans, are well known and have been attributed to multiple mechanisms of action. However, the lipolytic activity of CGAs does not appear to have been reported. We studied the effects of varying concentrations of Svetol®, a decaffeinated green coffee bean extract enriched in CGAs, on the liberation of free fatty acids from human adipocytes following short‐term (2 h) and long‐term (192 h) exposure. The results showed that although lipolytic activity observed following short‐term incubation could be tentatively linked to residual caffeine traces in the sample, longer‐term exposure clearly showed the effects of Svetol® on release of free fatty acids, and this effect was not due to caffeine. The results of this study provide a further mechanism by which to explain the long‐term health benefits of CGAs and Svetol®. Copyright © 2013 John Wiley & Sons, Ltd.